The Differential Performance of Wise Reasoning Among High School Students in Teacher–Student Conflict and Peer Conflict: A Psychometric Network Analysis - Lin, Hongyi; Wang, Yan; Wang, Fengyan (Psychology in the schools, 2025)
ABSTRACT As the primary location for adolescents' interpersonal communication, schools are an inevitable setting for interpersonal conflicts. This study aims to explore the differential performance of wise reasoning in both teacher–student and peer conflicts among high school students by network analysis, as well as the mediating roles of coping style. Data were collected from 1015 Chinese adolescents using a randomized trial design by self‐report measures. The mediation analysis demonstrated that problem coping orientation and emotional coping orientation played parallel mediating roles in the influence of conflict type on wise reasoning. Results of the network analysis showed that problem‐solving was the node with the strongest centrality in the network and had the highest bridge association degree with wise reasoning. “View of an outsider” and “Searching for a compromise” had the highest bridge association degrees with coping style. These findings enhanced our understanding of the differential performance of wise reasoning among high school students in different school conflict types. Future research should further explore these differences to develop more appropriate wisdom education for adolescents. Summary School conflicts serve as valuable educational tools and provide opportunities for cultivating wisdom in adolescents. Teacher–student conflict is more conducive to promoting adolescents' wise reasoning than peer conflict. Problem solve orientation is more conducive to promoting adolescents' wise reasoning than emotional coping orientation.